Modeling of three-phase uniform symmetrical sampling digital PWM for power converter - Mekhilef, Saad; Omar, A.M.; Rahim, N.A. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
A mathematical approach of modeling and analyzing three-phase pulsewidth modulation (PWM) is presented. The three-phase flyback converter required a unique pattern of PWM to optimize the power transfer in the magnetic circuit used in the converter. The three-phase PWM is generated digitally based on uniform symmetrical sampling technique using Xilinx chip. The generated PWM pattern is able to reduce the magnitude of the low order of harmonic components present in the input ac supply. Although software simulation could simulate the PWM pattern, it does not represent the exact pattern as being generated digitally. The mathematical approach used is to model the PWM pattern exactly as being created digitally. The proposed mathematical technique could also be used to analyze any digital PWM. The result of the mathematical analysis on the PWM pattern could be used to study the characteristics of the pattern such as maximum and minimum value of duty cycle, pulsewidth, turn-on time, turn-off time, and modulation index. To verify the validity of the proposed technique, the results obtained from the mathematical model, experimental, and simulation using PSpice were compared.